2005
DOI: 10.1177/0170840605057072
|View full text |Cite
|
Sign up to set email alerts
|

The Power of 'Organizational Culture' as a Discursive Formation in Merger Integration

Abstract: This paper argues that knowledge on 'organizational culture' has acquired authority and constitutes a 'truth' on mergers, a truth imbued with both enabling and constraining power effects. Taking a Foucauldian perspective, the paper theorizes 'organizational culture' as a discursive formation that is implicated in a regime of truth. This regime has involved a process of disciplinary normalization in merger integration with the result that 'culture' has become naturalized to 'organization'. Drawing on ethnograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 51 publications
2
88
0
6
Order By: Relevance
“…This approach shifts the focus beyond ideological considerations because there is no authentic or true self prior to the appearance of power. As such, the power of subjection lies the way it can create discursive or narrative 'truth effects' that are lived on an everyday subjective basis (Boje, 1995;Riad, 2005).…”
Section: Subjectification 'In' Organizationsmentioning
confidence: 99%
“…This approach shifts the focus beyond ideological considerations because there is no authentic or true self prior to the appearance of power. As such, the power of subjection lies the way it can create discursive or narrative 'truth effects' that are lived on an everyday subjective basis (Boje, 1995;Riad, 2005).…”
Section: Subjectification 'In' Organizationsmentioning
confidence: 99%
“…In contrast to the studies discussed above, several scholars have taken a critical perspective on the role of culture in PMI, identifying the limits and even biases inherent in studying cultural differences in this context (Riad, 2005;Risberg, 2001;Vaara, 2002;Vaara et al, 2014). Vaara et al (2014) examined managers' attributions regarding causes of PMI performance, and found that managers attributed failure -but not success -to cultural differences.…”
mentioning
confidence: 99%
“…This literature also tends to view culture during postmerger integration as an outcome of a premeditated integration approach (e.g., Bower, 2004;Haspeslagh & Jemison, 1991;Morosini & Singh, 1994;Nahavandi & Malekzadeh, 1988;Schweiger, 2002). Although the extant literature on culture clashes is overly deterministic, the constructionist approach posits that the impact of culture on postmerger integration is best explained through the discursive and sensemaking traditions of cultural theory (e.g., Gertsen, Soderberg, & Torp, 1998;Hellgren et al, 2002;Riad, 2005;Soderberg & Holden, 2002;Vaara, 2000Vaara, , 2002Vaara, , 2003. In this view, the merged cultures are social constructs that reflect both the context of identity construction and the social organization of meaning in postmerger integration.…”
Section: Contexts Of Equality: Cultural Differences In Mergers Of Equalsmentioning
confidence: 99%